First record of eleven Uropodina species from Slovenia (Acari: Mesostigmata) - Kontschán, J. (Acta entomologica slovenica (Ljubljana), 2009)
Eleven Uropodina species were collected from different parts of Slovenia. Original drawings, scanning micrographs and maps are given.
Keywords: entomologija; pršice; Slovenia; Slovenija